Operations Management : Sustainability and Supply Chain Management - Heizer, Jay; Rebder, Barry; Munson, Chuck and Sachan, Amit (Malaysia Pearson, 2020)
A brief, full-colour book, this work is intended to be non-threatening for an operations management course.
Include Illustrations, Table, Graphs, Diagrams and Index
Keywords: Business logistics